VIRUS NIPAH - Rampengan, Novie H. (JURNAL BIOMEDIK : JBM, 2016)
Abstract: Nipah virus caused outbreaks in Malaysia and Singapore in 2009 with a high mortality rates. It also erupted in Bangladesh, India, and the Philippines. Nipah virus infection varies from asymptomatic to severe manifestation with a mortality rate varies from 38% to 80%. Diagnosis can be confirmed by using reverse transcriptase-polymerase chain reaction (RT-PCR), immunohistochemical examination, enzyme-linked immunosorbent assay (ELISA), and neutralization test. There is still neither vaccine nor specific treatment for the Nipah virus so farKeywords: Nipah virus, signs and symptoms, diagnosisAbstrak: Virus Nipah menimbulkan outbreak di Malaysia dan Singapura tahun 2009 dengan angka kematian yang tinggi. Selain itu virus Nipah juga menimbulkan outbreak di Bangladesh, India, dan Filipina. Infeksi virus Nipah dapat bervariasi dari asimtomatik sampai bermanifestasi klinis yang berat dengan angka kematian bervariasi dari 38%-80%. Diagnosis dapat ditegakkan dengan reverse transcriptase-polymerase chain reaction (RT-PCR), pemeriksaan imunohistokimia, enzyme-linked immunosorbent assay (ELISA), dan tes netralisasi. Sampai saat ini belum ada vaksin dan terapi spesifik untuk virus Nipah.Kata kunci: virus Nipah, gejala, diagnosis